2010
DOI: 10.1182/blood.v116.21.170.170
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemotherapy with Rituximab Improves Molecular CR Rate and Outcome In CD20+ B-Lineage Standard and High Risk Patients; Results of 263 CD20+ Patients Studied Prospectively In GMALL Study 07/2003

Abstract: 170 The effect of Rituximab in conjunction with a chemo induction and consolidation therapy was studied in CD20+, Ph/BCR-ABL negative B-precursor ALL (Pre-B/Common) in the GMALL Study 07/2003. The rationale were encouraging results with combined intensive chemotherapy and Rituximab in CD20+ adult Burkitt lymphoma / leukemia. Furthermore that in previous GMALL studies, improvement of B-precursor ALL by intensification of chemotherapy was limited and the observation that patients with CD20+ cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 0 publications
3
19
2
2
Order By: Relevance
“…The GMALL also found an increase in survival and 5-year remission duration in patients younger than 55 years when rituximab was added to standard chemotherapy. 81,82 The incidence of MRD negativity improved with rituximab as well.…”
Section: Treatment Of Precursor B-cell Allmentioning
confidence: 97%
“…The GMALL also found an increase in survival and 5-year remission duration in patients younger than 55 years when rituximab was added to standard chemotherapy. 81,82 The incidence of MRD negativity improved with rituximab as well.…”
Section: Treatment Of Precursor B-cell Allmentioning
confidence: 97%
“…113 A further non-randomised study from the GMALL group also demonstrated a benefit in 263 patients receiving induction chemotherapy with added rituximab over historical outcomes, showing higher CR rates and improved 5-year OS for both standard and high-risk patients. 114 However, the veracity of conclusions based on comparison to historical data is far from ideal. Consequently, the GRALL-2005 study, undertaken from 2006 to 2014, is the only randomised trial of rituximab in the CD20+ (>20% by immunohistochemistry) Ph-ve B-ALL setting.…”
Section: Aggressive Hematological Malignanciesmentioning
confidence: 99%
“…Rituximab as a single agent had minimal activity in ALL but improved survival when combined with chemotherapy in CD20-positive ALL. [4][5][6][7][8] This encouraged investigational therapies with other monoclonal antibodies directed against ALL surface markers. 9,10 Inotuzumab ozogamicin is a CD22 monoclonal antibody bound to calicheamicin, a natural product of Micromonospora echinospora, which is significantly more toxic than cytotoxic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%